The equivalent expression is 5^(4) * 3^(-10)
<h3>How to determine the equivalent expression?</h3>
The statement is given as:
five raised to the negative second power times three raised to the fifth power end quantity all raised to the negative second power
Rewrite properly as:
(5^-2 * 3^5)^-2
Expand the expression by multiplying the exponents
So, we have:
5^(-2 -2) * 3^(5 *-2)
Evaluate the products
5^(4) * 3^(-10)
Hence, the equivalent expression is 5^(4) * 3^(-10)
Read more about expression at
brainly.com/question/723406
#SPJ1
When an exponential function is given as
f(x)=ab^x, and
knowing that b^0=1, that means that
f(0)=ab^0=a value of function when x=0, or the initial value.
In the case of
f(x)=20.b^x, f(0)=20.b^0 = 20 (initial value)
If b=1.2, then the hourly growth rate is (1.2-1)=0.2=20%.
If b=1.85, then the hourly growth rate is (1.85-1)=0.85=85%.
Hamburgers and spaghetti are preferred almost equally.